2021
DOI: 10.1093/nar/gkab770
|View full text |Cite
|
Sign up to set email alerts
|

A rapid method to visualize human mitochondrial DNA replication through rotary shadowing and transmission electron microscopy

Abstract: We report a rapid experimental procedure based on high-density in vivo psoralen inter-strand DNA cross-linking coupled to spreading of naked purified DNA, positive staining, low-angle rotary shadowing, and transmission electron microscopy (TEM) that allows quick visualization of the dynamic of heavy strand (HS) and light strand (LS) human mitochondrial DNA replication. Replication maps built on linearized mitochondrial genomes and optimized rotary shadowing conditions enable clear visualization of the progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…[ 23 ] The thickness of the metal casting is typically ≈8 nm for high‐contrast TEM images. [ 24 ] AFM studies have demonstrated that the diameter of DNA ranges between 5 and 10 nm, although they have also revealed a sub‐nanometer helical groove pattern within the DNA backbone. [ 25 ] Furthermore, several studies utilizing super‐resolution microscopy methods have been reported, with the finest resolution for DNA imaging being 45 nm using STED (Stimulated Emission Depletion), [ 8a ] 14 nm using BALM (Binding Activated Localization Microscopy), [ 8b ] 67 nm using STORM (Stochastic Optical Reconstruction Microscopy), [ 26 ] and 20 nm using Vortex PSF (Point Spread Function).…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] The thickness of the metal casting is typically ≈8 nm for high‐contrast TEM images. [ 24 ] AFM studies have demonstrated that the diameter of DNA ranges between 5 and 10 nm, although they have also revealed a sub‐nanometer helical groove pattern within the DNA backbone. [ 25 ] Furthermore, several studies utilizing super‐resolution microscopy methods have been reported, with the finest resolution for DNA imaging being 45 nm using STED (Stimulated Emission Depletion), [ 8a ] 14 nm using BALM (Binding Activated Localization Microscopy), [ 8b ] 67 nm using STORM (Stochastic Optical Reconstruction Microscopy), [ 26 ] and 20 nm using Vortex PSF (Point Spread Function).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we asked whether MPG affects APOE expression through binding to R-loops. Using the S9.6 antibody that specifically recognizes R-loops (Hu et al, 2006; Kosar et al, 2021), we carried out DNA-RNA immunoprecipitation, DRIP, followed by sequencing. Since APOE is not transcribed or at a very low level in fibroblasts, there was no RNA to form R-loops in APOE , rather we detected an R-loop upstream of APOE (Figure 2A, top panel), in an intergenic region.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the study of genomic DNA, EM has also been used to characterize the mitochondrial DNA replication cycle, as shown in Figure 1F. [41] Furthermore, DNA EM allows for visualization of various structures such as plasmid DNA, ss-ds DNA, ssDNA gap between dsDNA, holiday junction of DNA, D-loop, strand exchanges, and DNA intermediates formed during DNA damage repair. [33,42] 2.2.…”
Section: Dna Structures Under Emmentioning
confidence: 99%
“…F) Mitochondrial D-loops and some single-stranded DNA denaturation bubbles via uranyl acetate and Pt shadowing. Reproduced with permission [41]. Copyright 2021, Oxford University Press.…”
mentioning
confidence: 99%